Assessing the impact of inlet-outlet configurations on the hydraulics and treatment efficiency of floating treatment wetland retrofitted stormwater pond - Nuruzzaman, Md; Anwar, Faisal; Sarukkalige, Ranjan (2022)
Floating treatment wetland (FTW) is becoming increasingly popular for stormwater treatment. The flow field of an FTW retrofitted stormwater pond and treatment efficiency will depend on the design configurations. In this study, we investigated the impact of inlet-outlet configuration on the flow field of pond, hydraulic performance and treatment efficiency by FTW. Hydraulic tracer experiments were conducted in a 0.3 m3 tank for 13 cases with different inlet-outlet configurations and keeping the FTW (10% coverage) fixed at the center of the tank to estimate hydraulic performance of the cases. Simulations were performed for the same cases in ANSYS Fluent to determine treatment efficiency. It was revealed that inlets positioned away from the FTW along the transverse direction had lower hydraulic performance due to flow short-circuiting but generally higher treatment efficiency (up to 53%) compared to other cases. This was the result of high residence time of pollutant mass within FTW. When the inlets were positioned in line with the FTW, the high-velocity stream was intercepted by the FTW, but it reduced residence time within FTW and thus treatment efficiency even though the fraction of pollutant mass entry (85.5 – 100%) was increased in these cases. It signifies the importance of promoting the contact period between the inflow and FTW for a better treatment effect. Outlet positions also influenced hydraulic performance, flow field and treatment efficiency but to a lesser extent. Further research is required to understand the relationship between hydraulic performance and treatment efficiency of FTW retrofitted stormwater pond. The outcome of this study will help engineers and designers manipulate inlet-outlet configurations for efficient treatment by FTW.